A STUDY ON THE SATISFACTION OF EMPLOYEES OF STATE BANK OF TRAVANCORE TOWARDS ITS MERGER WITH STATE BANK OF INDIA WITH SPECIAL REFERENCE TO MALAPPURAM REGION - Ranzy.K.P & Dr.P.S.Chandni (International Journal of Research Science and Management, 2017)
The State Bank of Travancore (SBT) is officially State Bank of India (SBI) now, with its merger with the latter. Through mergers with its associate banks, SBI will benefit from better reach and network, and will find itself among the world’s largest banks. But it also risks ignoring local sensibilities. Though State Bank of India consolidation has many benefits, it’s not without pitfalls. The five banks recently merged with SBI are State Bank of Travancore, State Bank of Bikaner and Jaipur, State Bank of Mysore, State Bank of Hyderabad and State Bank of Patiala. SBI also absorbed Bharatiya Mahila Bank. One of the biggest challenges for the new entity will relate to human resources issues. The combined strength of all associate bank employees is estimated at around 70,000, or a third of SBI’s 2,10,000 strong personnel. The problem of integrating the staff is likely to be cumbersome. There are bound to be questions over seniority and given the public sector character of the banks, the courts might intervene. Pension liabilities will also surge. There is, however, one significant argument against the merger of the five banks with SBI that needs to be understood in the context of regional and local sensibilities over which the merger will ride roughshod. SBI associate banks cater to specific regions, as their nomenclature indicates. State Bank of Travancore, for instance, caters to the Travancore region predominantly, although of course not exclusively. Such specialization brings with it unique insights into local customs. This study focuses on analyzing the opinion of eSBT employees towards the merger and to identify the various measures taken by SBI to protect the interest of eSBT employees.